Analysis of Forest Carrying Capacity on Eos histrio in North Sulawesi - Nastitie Nastitie; Gantina Rachmaputri (Journal of the Indonesian Mathematical Society, 2021)
The International Union for the Conservation of Nature and Natural Resource (IUCN) Red List found that there are currently over 8.000 critically endangered species and the number seems likely to rise in the future. One of the species included in the IUCN Red List is Eos histrio, also known as the Red-and-blue lory, a bird endemic to Indonesia that inhabits Nusa Utara Islands, North Sulawesi. It lives in a forest with tall trees as its natural habitat. According to the Central Bureau of Statistics (BPS), the forest area is decreasing every year and has caused the bird to lose their habitats and its population is declining. IUCN also reported that there are 8.230 – 21.400 Eos histrio in 1999, however in 2016, it was only around 5.500 – 14.000. Its population will be declining due to extensive deforestation and poor conservation. Using Pontryagin maximum principle, this study found that one of the methods to protect the Eos histrio population is by reducing deforestation in North Sulawesi by at least 10% where the population of the bird could increase within a year.